Clinical characteristics of cystic fibrosis patients prior to lung transplantation: An international comparison between Canada and the United States. Issue 3 (11th February 2018) - Quon, Bradley S.; Sykes, Jenna; Stanojevic, Sanja; Marshall, Bruce C.; Petren, Kristofer; Ostrenga, Josh; Fink, Aliza; Elbert, Alexander; Faro, Albert; Goss, Christopher H.; Stephenson, Anne L.
Abstract: Background: Cystic fibrosis (CF) patients from Canada have better‐reported post–lung transplant survival compared to patients from the United States. We hypothesized the clinical characteristics of CF patients prior to lung transplant differ between the two countries. Methods: Population‐based cohort study utilizing combined Canadian CF Registry and US CF Foundation Patient Registry data from 1986 to 2013. Demographic and clinical variables were analyzed prior to lung transplant. Results: Between 1986 and 2013, 607 (10.2%) CF patients underwent lung transplantation in Canada and 3428 (7.5%) in the United States. A lower proportion of recipients had growth of B. cepacia complex prior to transplant in the United States compared to Canada (0.8% vs 4.3%). Lung function was similar between recipients from the two countries. The proportion of patients classified as underweight was significantly higher in the United States compared to Canada (39.8% vs 28.0%; SD 26.1) despite higher rates of feeding tube use (42.5% vs 28.6%; SD 29.0). Conclusions: CF lung transplant recipients from the United States have similar lung function, lower rates of B. cepacia complex, and worse nutritional parameters prior to transplant compared to counterparts in Canada. Future studies are necessary to evaluate the impact of these differences on post‐transplant survival.